La transitional care di adolescenti con malattie rare - Perino, Annamaria; Braida, Nicole (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
The article approaches the subject of transitional care, presenting the first phase of a project dedicated to teenagers with rare diseases. Research began in March of 2012 at the Regina Margherita Children’s Hospital of Turin. The project, whose objective is to compensate for the lack of attention of the Italian Health Care System to the needs of adolescent patients with chronic or rare diseases, started with a qualitative survey whose aim was to explore the needs and expectations of key stakeholders (health professionals, patients and parents). The results suggest the need to promote a change in cultural outlook which will prepare doctors, patients and their family members to the transition from pediatric to adult services. Adolescents should be considered as persons who are neither children, grownups nor small adults, but as persons who require specific, integrated responses provided by different professionals.